Figures of merit guiding research on organic solar cells - Kirchartz, T; Kaienburg, P; Baran, D (American Chemical Society, 2018)
While substantial progress in the efficiency of polymer-based solar cells was possible by optimizing the energy levels of the polymer and more recently also the acceptor molecule, further progress beyond 10% efficiency requires a number of criteria to be fulfilled simultaneously, namely, low energy-level offsets at the donor–acceptor heterojunction, low open-circuit voltage losses due to nonradiative recombination, and efficient charge transport and collection. In this feature article we discuss these criteria considering thermodynamic limits, their correlation to photocurrent and photovoltage, and effects on the fill factor. Each criterion is quantified by a figure of merit (FOM) that directly relates to device performance. To ensure a wide applicability, we focus on FOMs that are easily accessible from common experiments. We demonstrate the relevance of these FOMs by looking at the historic and recent achievements of organic solar cells. We hope that the presented FOMs are or will become a valuable tool to evaluate, monitor, and guide further development of new organic absorber materials for solar cells.